(untitled) (Research, Society and Development, 2020)
The transmissible venereal tumor (TVT) is well-documented and researched in dogs due to the unique characteristic of its transmissible cells. Despite of the vast scientific literature regarding genital TVT, the extragenital TVT is also present in many endemic countries, but the scientific descriptions about this disease came from isolated reports and case series. Thus, the objective of this study was to gather all the national and international information available of extragenital TVT in dogs and analyze it in the form of a systematic review, aiming understanding the countries with the highest incidence of cases, the relationship with the patients’ review (race, sex and age), genital involvement, extragenital location, choice treatment and evolution of the disease. The results demonstrated 134 cases of the extragenital TVT with 214 extragenital lesions. The most of the studies came from Europe and South America. The mixed-bred dogs and males ranging from one to five years-old were the most commonly diagnosticated. The external organs were frequently affected and the ascendant tumor infiltration seemed was rare. The vincristine was the treatment of choice in almost all patients, having a complete remission in 79% of reported cases. In addition, it was observed that multiple lesions and chemoresistance can have a negative impact on the prognosis of this disease.